The unavoidable salience of gender: notes from Australian childcare work. Issue 12 (1st December 2016) - Andrew, Yarrow
Abstract: This article explores the gendering of work in Australian childcare settings from a post-gender perspective. Much early childhood research focuses on encouraging men into the field, seeing their presence as beneficial to the perceived worth of childcare work. Such research ignores how women's gendered experiences, as the overwhelming majority of the workforce, are already shaping the field, creating an image of this work apparently unpalatable to most men. I show how gendered relations have a profound impact, even in mono-gendered spaces like childcare, to the continuing disadvantage of women. Workers caught within binary understandings of gender appear to draw on normative gendered discourses to understand the social and economic positioning of the field, rather than more emancipatory framings. This article argues that perspectives that actively question biomedical understandings of gender can be useful in understanding and challenging the gendering of particular societal spaces, such as childcare services.